Let $H$ and $K$ be subgroups of a group $G$. My question is: when is $$ HK = \{hk: h\in H, k\in K\} $$ a subgroup of $G$?

If $G$ is abelian, then this is clearly the case. I believe I have shown that if $H$ and $K$ are both normal subgroups of $G$, then $HK$ is a subgroup.

Are there any more general results where this is the case?

I do see things like this giving a list of equivalent statements, but I was wondering what statements imply that $HK$ is a subgroup.

| cite | improve this question | | | | |
  • 7
    $\begingroup$ It is enough for one of $H,K$ to be normal. But that is not a necessary condition. You can have $HK=G$ for example. $\endgroup$ – almagest Feb 20 '18 at 13:08
  • 5
    $\begingroup$ In general, $HK$ is a subgroup if and only if $HK=KH$. $\endgroup$ – Derek Holt Feb 20 '18 at 13:09
  • $\begingroup$ @almagest: and it doesn't matter which one? $\endgroup$ – John Doe Feb 20 '18 at 13:09
  • 2
    $\begingroup$ @DerekHolt the OP knows that, he is after sufficient conditions that are not in the Wikipedia article. $\endgroup$ – Arnaud Mortier Feb 20 '18 at 13:09
  • $\begingroup$ @almagest: Please write this as an answer so that I can accept something. $\endgroup$ – John Doe Feb 26 '18 at 13:30

We use the result provided by Goldy. We can show the following corollary.

Corollary. Let $H$ and $K$ be subgroups of a group $G$. (a) If $H\leq N_{G}(K)$, then $HK$ is a subgroup of $G$. (b) If $K\unlhd G$ then $HK\leq G$.

Proof. (a) We show that $HK=KH$.

$HK \subset KH$: let $h\in H$ and $k\in K$. Then $h\in N_{G}(K)$. So $hKh^{-1}=K$. Hence $hkh^{-1}=l$ for some $l\in K$. So $hk=lh\in KH$.

$KH\subset HK$: let $k\in K$ and $h\in H$. Then $h^{-1}\in N_{G}(K)$. So $h^{-1}kh=l$ for some $l\in K$. Hence $kh=hl\in HK$.

So $HK=KH$. By the result provided by Goldy, $HK\leq G$.

(b) Since $K\unlhd G$, we have $gKg^{-1}=K$ for all $g\in G$. So $N_{G}(K)=G$. Hence $H\leq N_{G}(K)$. By part (a), $HK\leq G$.

Corollary. Let $H$ and $K$ are subgroups of a group $G$. (a) If $H\leq N_{G}(K)$ or $K\leq N_{G}(H)$, then $HK\leq G$. (b) If $H\unlhd G$ or $K\unlhd G$, then $HK\leq G$.

Proof. (a) If $H\leq N_{G}(K)$, then by the first corollary, $HK\leq G$. If $K\leq N_{G}(H)$, then by the first corollary, $KH\leq G$. By the previous result, $HK=KH$. So $HK\leq G$.

(b) If $K\unlhd G$, then $HK\leq G$. If $H\unlhd G$, then $KH\leq G$. So $HK=KH\leq G$.

Edit: one more case.

Corollary. Let $H$ and $K$ be subgroups of a group $G$. If $H\subset K$ or $K\subset H$, then $HK\leq G$.

Proof. If $H\subset K$, then $K\subset HK\subset K$. So $HK=K\leq G$. If $K\subset H$, then $H\subset HK\subset H$. So $HK=H\leq G$.

| cite | improve this answer | | | | |

$HK$ is a subgroup of $G$ iff $HK=KH$.

Let $HK$ be a subgroup of $G$. If $x\in HK$ is any element, then $x^{-1}\in HK$. This implies, $x^{-1}=hk \implies x=k^{-1}h^{-1}\in KH$. Thus, $HK\subseteq KH$. Similarly, $KH\subseteq HK$. Hence, $HK=KH$.

Conversely, let $KH=HK$. Let $x,~y\in HK$. Then $x=h_1k_1$ and $y=h_2k_2$ for some $h_1,h_2\in H$, $k_1,k_2\in K$. This implies, $xy^{-1}=h_1(k_1k_2^{-1})h_2^{-1}$. Now, $(k_1k_2^{-1})h_2^{-1}\in KH=HK$, thus $(k_1k_2^{-1})h_2^{-1}=hk$ for some $h\in H$, $k\in K$. Thus, $xy^{-1}=h_1(hk)=(h_1h)k\in HK$. Hence, $HK$ is a subgroup, as $x, y\in HK\implies xy^{-1}\in HK$.

| cite | improve this answer | | | | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.